2016
DOI: 10.1016/j.jneb.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Assessment of Printed Dietary Guidelines for Pregnant Women and Parents of Infants and Toddlers From 7 European Countries

Abstract: Overall, the suitability of the assessed printed dietary guidelines was adequate. Based on the SAM methodology, printed dietary guidelines may increase in suitability by emphasizing aspects related to health literacy and accommodating the needs of different food cultures within a population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The SAM instrument is a validated method for evaluating written health-related educational materials. It is used to evaluate printed materials in terms of categories and factors known to enhance people's understanding of printed material (31).…”
Section: Discussionmentioning
confidence: 99%
“…The SAM instrument is a validated method for evaluating written health-related educational materials. It is used to evaluate printed materials in terms of categories and factors known to enhance people's understanding of printed material (31).…”
Section: Discussionmentioning
confidence: 99%
“…When previous studies assessed the suitability of health information across multiple sources, the converted percent was also applied to the present the quality of the health information per SAM criterion [ 47 , 48 ]. In this study examining which criterion was suitably met across the websites, the mean score per criterion was computed and then converted to a percent of the possible best score using the following formula: the converted percent=([n of websites×0 point]+[n of websites×1 point]+[n of websites×2 points])/Total possible best score (84=42 websites×2 points)×100.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the use of picture books as a medium could be expected to be an opportunity to promote intergenerational understanding between elders and young children. At the same time, however, research has shown that teaching materials such as health education books tend to pay little attention to their applicability to the intended target population (Garnweidner-Holme et al, 2016). Therefore, this study is an attempt to use a stakeholder engagement design (stakeholder engagement), which emphasizes multicultural teamwork between all product stakeholders to provide ideas or allows them to be directly involved in the event development process (Goodman & Sanders Thompson, 2017), in order for the materials to be relevant to the needs of future users (Aner, 2016).…”
Section: Introductionmentioning
confidence: 99%